Identification of four novel DC-SIGN ligands on Mycobacterium bovis BCG - Carroll, Maria V.; Sim, Robert B.; Bigi, Fabiana; Jäkel, Anne; Antrobus, Robin; Mitchell, Daniel A. (Springer, 2019)
Dendritic-cell-specific intercellular adhesion molecule-3-grabbing non-integrin (DC-SIGN; CD209) has an important role in mediating adherence of Mycobacteria species, including M. tuberculosis and M. bovis BCG to human dendritic cells and macrophages, in which these bacteria can survive intracellularly. DC-SIGN is a C-type lectin, and interactions with mycobacterial cells are believed to occur via mannosylated structures on the mycobacterial surface. Recent studies suggest more varied modes of binding to multiple mycobacterial ligands. Here we identify, by affinity chromatography and mass-spectrometry, four novel ligands of M. bovis BCG that bind to DC-SIGN. The novel ligands are chaperone protein DnaK, 60 kDa chaperonin-1 (Cpn60.1), glyceraldehyde-3 phosphate dehydrogenase (GAPDH) and lipoprotein lprG. Other published work strongly suggests that these are on the cell surface. Of these ligands, lprG appears to bind DC-SIGN via typical proteinglycan interactions, but DnaK and Cpn60.1 binding do not show evidence of carbohydrate-dependent interactions. LprG was also identified as a ligand for DC-SIGNR (L-SIGN; CD299) and the M. tuberculosis orthologue of lprG has been found previously to interact with human toll-like receptor 2. Collectively, these findings offer new targets for combating mycobacterial adhesion and within-host survival, and reinforce the role of DCSIGN as an important host ligand in mycobacterial infection.